The Influence of Organizational Culture, Work Discipline, Training Programs and Trust on Employee Performance - Kustini, Endang; Yusnita, Nancy; Sunaryo, Widodo (ADPEBI Publisher, 2025)
Purpose – This study aims to determine the effect of organizational culture, work discipline, training programs and trust on employee performance. Methodology/approach – The population in this study were all Civil Servants in Functional Positions at the Ministry of Cooperatives and SMEs of the Republic of Indonesia totaling 253 employees. The sampling technique used proportional random sampling with the Slovin formula with an error margin of 5% with a sample size of 155 respondents. The data analysis method used in this study was multiple linear regression. Findings – The results of this study are that there is a significant positive effect of Organizational Culture on Employee Performance. There is a significant positive effect of Work Discipline on Employee Performance. There is a significant positive effect of Training Programs on Employee Performance. There is a significant positive effect of Trust on Employee Performance. Simultaneously there is a significant positive effect of organizational culture, work discipline, training programs, and trust on employee performance.